Seladoeneolignan A, a new neolignan from Selaginella doederleinii Hieron. - Minyu CHEN; Ni ZHENG; Wenqi LIU; Dingrong WAN; Rumei LU; Xinzhou YANG (KeAi Communications Co., Ltd., 2022)
Objective: To study the chemical compositions from Selaginella doederleinii Hieron. Methods: The petroleum ether and ethyl acetate fractions of 80% ethanol extract of S. doederleinii were separated and purified by macroporous resin, silica gel, Sephadex LH-20 and semi-preparative HPLC, and then the structures of obtained compounds were identified by physicochemical properties and spectroscopical data. Results: A total of 7 compounds were isolated and identified as seladoeneolignan A (1), ethoxy-ferulate (2), 11-dien-19-oic acid (3), aurantiamide (4), 9,16-dioxo-10,12,14-octadeca-trienoic acid (5), amentoflavone (6), and 7,4'-di-0-methylrobustaflavone (7). Conclusion: Compound 1 was a new neolignan obtaind from S. doederleinii for the first time. Compounds 1, 6 and 7 were screened for antitumor activity in vitro, and the testing results showed that 3 compounds had low inhibitory activity on Hep-2 and Eca-109 tumor cells.